Relationship Patterns, Stress Factors and Index the Time of the Teenage Women's Body to the Event Dysmenorrhea in Nutrition Students of Poltekkes Kaltim - Solimah Hayati; Jamil Anshory; Satriani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The high incidence of dysmenorrhea in adolescents has received less attention from themselves and the community, because adolescents only accept the pain as a natural thing. This study was to determine the relationship between diet, stress factors and body mass index of adolescent girls on the incidence of dysmenorrhea in students of nutrition study program at Poltekkes Kaltim 2022. The study used the Analytical Observational method with a cross sectional design study. Location on campus nutrition room 3. The results showed that there was a relationship between diet and the incidence of dysmenorrhea with a p-value of 0.010. The absence of a stress factor relationship obtained a p-value of 0.126. There is no relationship between BMI and the incidence of dysmenorrhea with a p-value of 0.408. In this study, there is a relationship between diet and the incidence of dysmenorrhea, and there is no relationship between stress factors and BMI on the incidence of dysmenorrhea in students of nutrition study program at Poltekkes Kaltim.